Quantitative Psychology Curriculum Design A Case Study At The Faculty Of Psychology Syarif Hidayatullah State Islamic University Jakarta - Suryadi, Bambang (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2015)
The need for quantitative psychology in the 21st century is an urgent need for Muslim psychologists to compliment what has been done in term of normative qualitative study. The weakness of Muslims psychologists in mastering the quantitative psychology results in the difficulty of measuring psychological dimensions, such as the dimensions of gratitude, tolerance and so forth. This paper aims to describe the curriculum design of quantitative psychology and the application of the curriculum in teaching and learning process at the Faculty of Psychology Syarif Hidayatullah State Islamic University Jakarta. This study used qualitative method in gathering and analyzing the data. The findings of the study indicates that the concrete activities of quantitative psychology can be initiated by developing psychological instruments measuring psychological variables such as patience, gratitude, tolerance, religiosity, spiritual awareness, spiritual commitment, and spiritual intelligence.